THE EFFECT OF USING FACEBOOK PROFILE TOWARDS THE STUDENTS’ WRITING SKILLS IN DESCRIPTIVE TEXT AT SMA N 1 PURBATUA - Ummi Damayanti Panggabean (BRIGHT VISION Journal of Language and Education, 2021)
This study deals with The Effect of Using Facebook Profile toward the Students’ Writing Skill in Descriptive Text at SMA Negeri 1 Purbatua. The objective of this study is to find out whether Facebook Profile as a medium of learner has significant effect towards the students’ writing skills in descriptive text at SMA N 1 Purbatua. The total of population was 157 students and the researcher took 40 students as the sample of this research. Therefore, the researcher divided the class into two classes, there are experimental class and control class. The experimental class was applying Facebook Profile on the learning process meanwhile the control class was applying conventional. The data were collected by using both pre-test and post-test. The finding showed that the students who taught by using Facebook Profile got higher score than those who taught by conventional. The result showed that there was significant effect of using Facebook Profile on the students’ writing skill in descriptive text was proven for the result of analysis tobserved was higher than ttable (6,47  0.05) and df  38.  It  means the hypothesis alternative (ha) was accepted.Keywords: Facebook Profile, Descriptive Text, Effect